Grahama Priesta parakonsystentna metafizyka zmiany - Poczobut, Robert (Filozofia Nauki, 1998)
The article provides a critical analysis of G. Priest’s logical-philosophical views concerning contradictions holding at nodal points of certain kinds of changes. His position is confronted with the results of K. Ajdukiewicz’s studies regarding the 208 Summaries paradoxes of motion. Priest’s arguments advocationg the existence of contradictions in the realm of real world are here considered not only highly speculative but also based on doubtful theoretical principles (such as LCC - Leibniz Continuity Condition).